Epoxy-Based Composites - Jerold Samuel Chelladurai, Samson; Arthanari, Ramesh (IntechOpen, 2022)
Epoxy-based composites are used in automotive and aerospace applications because of their high strength-to-weight ratio, high stiffness-to-weight ratio, and good resistance to wear and corrosion. This book presents research on epoxy-based composites and their applications. It explains methods of preparing and testing these composites, including the hand lay-up technique, compression molding, and others. This book is useful for industrialists, undergraduate and postgraduate students, research scholars, and scientists.